EXECUTION OF THE DECISION OF THE COMMERCIAL COURT IN THE PROCEDURE OF JUDICIAL CONTROL OVER THE EXECUTION OF THE COURT DECISION - Ивасин, Александр (SWorldJournal, 2021)
The author considers the peculiarities of the execution of the decision of the commercial court in the exercise of judicial control over the execution of the court decision. The content of the concept of "judicial control" is revealed and the topical iss